PAD-2-mediated citrullination of nucleophosmin provides an effective target for tumor immunotherapy. Issue 2 (9th February 2022) - Choudhury, Ruhul H; Symonds, Peter; Paston, Samantha J; Daniels, Ian; Cook, Katherine W; Gijon, Mohamed; Metheringham, Rachael L; Brentville, Victoria A; Durrant, Lindy G
Abstract : Background: The enzymatic conversion of arginine to citrulline is involved in gene and protein regulation and in alerting the immune system to stressed cells, including tumor cells. Nucleophosmin (NPM) is a nuclear protein that plays key roles in cellular metabolism including ribosome biogenesis, mRNA processing and chromatin remodeling and is regulated by citrullination. In this study, we explored if the same citrullinated arginines within NPM are involved in gene regulation and immune activation. Methods: HLA-DP4 and HLA-DR4 transgenic mice were immunized with 22 citrullinated NPM overlapping peptides and immune responses to the peptides were assessed by ex vivo ELISpot assays. Antitumor immunity of NPM targeted vaccination was assessed by challenging transgenic mice with B16F1 HHDII/iDP4, B16F1 HHDII/PAD2KOcDP4, B16F1 HHDII and Lewis lung carcinoma cells/cDP4 cells subcutaneously. Peripheral blood mononuclear cells isolated from healthy donors were stimulated with NPM266-285cit peptides with/without CD45RO+memory cell depletion to assess if the responses in human were naïve or memory. Results: In contrast to NPM regulation, which is mediated by peptidylarginine deiminase (PAD4) citrullination of arginine at position 197, only citrullinated NPM266-285 peptide induced a citrulline-specific CD4 T cell response in transgenic mice models expressing human HLA-DP4 or HLA-DR4. Vaccinations with the NPM266-285cit peptide stimulated antitumor responses that resulted in dramatic tumor therapy, greatly improved survival, and protected against rechallenge without further vaccination. The antitumor response was lost if MHCII expression on the tumor cells was knocked out demonstrating direct presentation of the NPM266-285cit epitope in tumors. This antitumor response was lost in B16 tumors lacking PAD2 enzyme indicating NPM266cit is citrullinated by PAD2 in this model. Assessment of the T cell repertoire in healthy individuals and patients with lung cancer also showed CD4 T cells that respond to NPM266-285cit. The proliferative CD4 responses displayed a Th1 profile as they were accompanied with increased IFNγ and granzyme B expression. Depletion of CD45RO+ memory cells prior to stimulation suggested that responses originated from a naïve population in healthy donors. Conclusion: This study indicates PAD2 can citrullinate the nuclear antigen NPM at position 277 which can be targeted by CD4 T cells for antitumor therapy. This is distinct from PAD4 citrullination of arginine 197 within NPM which results in its transport from the nucleoli to the nucleoplasm.